ANALISIS FAKTOR KEPUTUSAN WISATA BUDAYA, SEJARAH DAN ALAM YOGYAKARTA: PERSEPSI WISATAWAN DOMESTIK - Anggi Rahajeng (Universitas Islam Indonesia, 2008)
This study is conducted to identify factors that influence the decision of tourists to visit Yogyakarta using factor analysis technique. Further, this study attempts to explore the perception of touristst on tourism in Yogyakarta. Yogyakarta’s tourism have three main recreation’s attributes: culture, history, and nature. Empirical results show that, overall, visitors are satisfied with the services provided in selected recreational sites. However there has been a lack in facilities and diversification of recreational activities. Therefore, some factors such as accommodation, satisfaction and recreational spot services become important aspects to attract visitors. Keywords: factor analysis technique, recreation’s attributes